PENERAPAN TEKNOLOGI TEPAT GUNA AUTOMATIC FEEDER BAGI MASYARAKAT PEMBUDIDAYA IKAN DI DESA SIBAU HILIR KECAMATAN PUTUSSIBAU UTARA - Juanda, Eki; Sukendar, Windu; Hasrah; Pratama, Wahyu Wira; Nofembrianti; Nasir, M.; Muhamad, Abah; Susanti, Lusi (Jurnal Abdi Insani, 2024)
The application of feeding management is frequency setting of feeding, namely the number of times the feed gave in a day. The farmers generally provide feed in aquaculture activities based on habits without knowing about the nutritional needs of fish, such as quality, quantity and the right time of supply. The weakness of manual feeding is the inaccuracy and efficiency of both the timing of feeding and the amount of feed given to the fish. In order that will be have an impact on the growth and water quality of the culture media. The purpose of this community service activity is for the people in Sibau Hilir village to know and be able to carry out fish farming activities by implementing a renewable automatic feeder technology system. The method used in this activity was focus group discussion (FGD) by conveying information to farmers regarding how was to use fish auto feeder technology with an electric timer system and also demonstrations for the operation of automatic fish feed machine technology. The result of this PPM activity is to increase the ability of fish farmers to master renewable technology in proper, easy, practical, and controlled feed management. The improving the efficiency of fish farming business used appropriate technology that is simple and inexpensive. Based on surveys before and after community service activities regarding automatic feeder technology, it turns out that there has been an increase in understanding and skills from initially not understanding to understanding the use of this technology. In addition, besides the discussions regarding the use of automatic feeder technology, a simple illustration on how to use it to the participants could better understand how the mechanical feeder technology works. The application of automatic feeder machines in cultivation activities expected to improve the skills of cultivators in Sibau Hilir village, thereby increasing the welfare of cultivators.